Kelvin : life, labours and legacy - Flood, Raymond; McCartney, Mark, 1967-; Whitaker, Andrew, 1946- (Oxford : Oxford University Press, 2008)
This work contains a collection of chapters, authored by leading experts, which cover the life and wide-ranging scientific contributions made by William Thomson, Lord Kelvin (1824-1907).
Includes bibliographical references and index.
Description based on print version record.
Keywords: Kelvin, William Thomson, -- Baron, -- 1824-1907.; Physicists -- Great Britain; Physics -- History -- 19th century